Program Perhitungan Upah Tenaga Kerja pada Proyek Konstruksi Menggunakan Bahasa Pemograman Visual Basic.Net - Meri Sufina (Universitas Putra Indonesia YPTK Padang, 2021)
Computer technology enters all fields including civil engineering. There have been many computer applications in civil engineering such as AutoCAD, Google Sketcup, SAP 2000, ETABS, etc. Utilization of computer technology can help various activities, one of them is construction project work. Many things cause delays in construction work, one of which is the problem of paying workers. Calculation of labor wages that still manually cause delays in payment of wages. Then a program for calculating labor wages in construction projects was made to support the construction project. This program uses visual basic.NET programming language by collecting data, designing programs and followed by making program codes to produce thedesired construction wage calculation program.